Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

The general form of the equation of a circle is [tex]Ax^2 + By^2 + Cx + Dy + E = 0[/tex], where [tex]A = B \neq 0[/tex]. If the circle has a radius of 3 units and the center lies on the [tex]y[/tex]-axis, which set of values of [tex]A, B, C, D[/tex], and [tex]E[/tex] might correspond to the circle?

A. [tex]A = 0, B = 0, C = 2, D = 2[/tex], and [tex]E = 3[/tex]
B. [tex]A = 1, B = 1, C = 8, D = 0[/tex], and [tex]E = 9[/tex]
C. [tex]A = 1, B = 1, C = 0, D = 8[/tex], and [tex]E = ?[/tex]
D. [tex]A = 1, B = 1, C = -8, D = 0[/tex], and [tex]E = 0[/tex]
E. [tex]A = 1, B = 1, C = 8, D = 8[/tex], and [tex]E = 3[/tex]


Sagot :

To solve the problem, we need to start by recalling the geometric properties and equations associated with a circle.

1. General Form of the Circle
The general form of a circle’s equation in Cartesian coordinates is:
[tex]\[ Ax^2 + By^2 + Cx + Dy + E = 0 \][/tex]
Given in the problem, [tex]\( A = B \neq 0 \)[/tex].

2. Standard Form of the Circle
The standard form of a circle with center at [tex]\((h, k)\)[/tex] and radius [tex]\( r \)[/tex] is:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]

3. Converting General Form to Standard Form
Since [tex]\(A = B = 1\)[/tex],
[tex]\[ x^2 + y^2 + Cx + Dy + E = 0 \][/tex]

We need to complete the square to convert this into the standard form.

4. Determine Center and Radius Conditions
Given:
- The radius [tex]\( r = 3 \)[/tex].
- The center of the circle lies on the [tex]\( y \)[/tex]-axis, so [tex]\( h = 0 \)[/tex].

Hence, the center is at [tex]\( (0, k) \)[/tex].

5. Equation in Standard Form
For a circle centered at [tex]\( (0, k) \)[/tex], the equation in standard form becomes:
[tex]\[ (x - 0)^2 + (y - k)^2 = 3^2 \][/tex]
[tex]\[ x^2 + (y - k)^2 = 9 \][/tex]
Expanding this:
[tex]\[ x^2 + y^2 - 2yk + k^2 = 9 \][/tex]

6. Match Coefficients to General Form
Compare this with the general form:
[tex]\[ x^2 + y^2 + Cx + Dy + E = 0 \][/tex]

Since there is no [tex]\( x \)[/tex]-term in the standard form, we have [tex]\( C = 0 \)[/tex].
For the [tex]\( y \)[/tex]-term, we have [tex]\( -2yk = Dy \)[/tex] implying [tex]\( D = -2k \)[/tex].
For the constants: [tex]\( k^2 - 9 = E \)[/tex].

7. Results Analysis
Look at various options and compare:
- Option A: [tex]\( A = 0, B = 0, C = 2, D = 2, E = 3 \)[/tex] – Incorrect, as [tex]\( A \)[/tex] and [tex]\( B \)[/tex] should both be 1.
- Option B: [tex]\( A = 1, B = 1, C = 8, D = 0, E = 9 \)[/tex] – The values [tex]\( C = 8\)[/tex] and [tex]\(D = 0 \)[/tex] do not match our derived results.
- Option C: [tex]\( A = 1, B = 1, C = 0, D = 8, E = ? \)[/tex] – Checking these values:
The coefficient [tex]\( C = 0 \)[/tex] is consistent. For [tex]\( D = 8\)[/tex], [tex]\( -2k = 8\)[/tex], giving [tex]\( k = -4 \)[/tex]. Thus, we calculate [tex]\( E = k^2 - 9 \rightarrow (-4)^2 - 9 = 16 - 9 = 7 \)[/tex]. Hence, [tex]\( E = -7\)[/tex].
- Option D: [tex]\( A = 1, B = 1, C = -8, D = 0, E = 0 \)[/tex] – Incorrect calculation from base requirement.
- Option E: [tex]\( A = 1, B = 1, C = 8, D = 8, E = 3 \)[/tex] – Incorrect base components.

8. Conclusion
The correct values, tested for option C, ensure that:
[tex]\[ A = 1, B = 1, C = 0, D = 8 \][/tex] and the derived value [tex]\( E = 0\)[/tex].

Thus, the correct set is:
[tex]\[ \boxed{C: A = 1, B=1, C=0, D=8, E=0} \][/tex]